2022
DOI: 10.1155/2022/9084283
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Transmission Dynamics of Meningitis among High and Low-Risk People in Ghana with Cost-Effectiveness Analysis

Abstract: Meningitis is an inflammation of the meninges, which covers the brain and spinal cord. Every year, most individuals within sub-Saharan Africa suffer from meningococcal meningitis. Moreover, tens of thousands of these cases result in death, especially during major epidemics. The transmission dynamics of the disease keep changing, according to health practitioners. The goal of this study is to exploit robust mechanisms to manage and prevent the disease at a minimal cost due to its public health implications. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Their results suggested that desert dust may have a significant impact on the onset to the peak of the meningitis season in Senegal, and re-iterate the critical need for more PM, meteorological, and meningitis measurements in West Africa to further resolve these relationships. Opoku et al (2022) remarked on the changing nature of the transmission dynamics of the disease and attempted exploitation of robust mechanisms to manage and prevent the disease at a minimal cost in the context of its public health implications, by use of a mathematical model. As a case in point, between January and May 2012, Senegal experienced an increase in meningitis cases during high concentrations of Saharan dust (Diokhane et al, 2016).…”
Section: Bacterial Meningitismentioning
confidence: 99%
“…Their results suggested that desert dust may have a significant impact on the onset to the peak of the meningitis season in Senegal, and re-iterate the critical need for more PM, meteorological, and meningitis measurements in West Africa to further resolve these relationships. Opoku et al (2022) remarked on the changing nature of the transmission dynamics of the disease and attempted exploitation of robust mechanisms to manage and prevent the disease at a minimal cost in the context of its public health implications, by use of a mathematical model. As a case in point, between January and May 2012, Senegal experienced an increase in meningitis cases during high concentrations of Saharan dust (Diokhane et al, 2016).…”
Section: Bacterial Meningitismentioning
confidence: 99%